2021
DOI: 10.1109/ojemb.2021.3104261
|View full text |Cite
|
Sign up to set email alerts
|

Stand-Up, Squat, Lunge, and Walk With a Robotic Knee and Ankle Prosthesis Under Shared Neural Control

Abstract: We propose a shared neural control approach combining neural signals from the user's residual limb with robot control to improve functional mobility in individuals with above-knee amputation. The proposed shared neural controller enables subjects to stand up under a variety of conditions, squat, lunge, walk, and seamlessly transition between activities which is not possible with other prostheses or controllers. Further, we show that the proposed shared neural controller reduces muscle effort and increased symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…In contrast, powered ankles can actively dorsiflex before the stand-up movement begins and allow the user to select a natural starting position. This functional difference may be the underlying reason why the only significant improvements in weight bearing symmetry and muscle effort during stand-up with powered prosthetics have been shown in studies with powered knees combined with powered ankles [14], [15]. Future studies should investigate the role of the ankle by controlling the ankle torque based on ablebodied ankle torque profiles, including testing increased ankle torque with and without corresponding increases in knee torque.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, powered ankles can actively dorsiflex before the stand-up movement begins and allow the user to select a natural starting position. This functional difference may be the underlying reason why the only significant improvements in weight bearing symmetry and muscle effort during stand-up with powered prosthetics have been shown in studies with powered knees combined with powered ankles [14], [15]. Future studies should investigate the role of the ankle by controlling the ankle torque based on ablebodied ankle torque profiles, including testing increased ankle torque with and without corresponding increases in knee torque.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study with a research powered knee and powered ankle combined significantly improved weight-bearing symmetry, although some subjects needed to use armrests while standing up, decreasing the reliability of the results [14]. A recent case series with a TNSRE-2022-00328.R2 powered knee and powered ankle has shown improved weightbearing symmetry and muscle effort during standing-up using a proportional electromyographic (EMG) controller, with the subject directly controlling the amount of assistance at each point in time [15]. However, we still lack essential knowledge about how to tune powered prostheses to best assist users.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral above-knee amputation severely limits ambulation ability and quality of life 1 , 3 , 4 . Powered prostheses have the potential to address this problem by closely replicating the biomechanical functions of the missing legs during virtually all ambulation activities 17 , 18 , 23 , 24 , 28 . Two previous case studies 15 , 16 have shown that powered knee and ankle prostheses can enable an individual with bilateral above-knee amputation to walk on level ground.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the state machine and echo control strategies, in the past few years, significant efforts have also been made using electromyography (EMG) from residual-limb muscles to classify user intent and then impose a pre-determined gait trajectory. Progress using this method has been demonstrated in [12], [21]- [23] and [17]. Furthermore, in recent times with the improvement in processing power of onboard computers, computer vision and range sensors, have also been proposed to improve classification accuracy, as shown in [24], [25] and [26].…”
Section: Introductionmentioning
confidence: 99%